20 mJ, 1 ps Yb:YAG thin-disk regenerative amplifier - Alismail, Ayman; Wang, Haochuan; Brons, Jonathan; Fattahi, Hanieh (Journal of Visualized Experiments, 2017)
This is a report on a 100 W, 20 mJ, 1 ps Yb:YAG thin-disk regenerative amplifier. A homemade Yb:YAG thin-disk, Kerr-lens mode-locked oscillator with turn-key performance and microjoule-level pulse energy is used to seed the regenerative chirped-pulse amplifier. The amplifier is placed in airtight housing. It operates at room temperature and exhibits stable operation at a 5 kHz repetition rate, with a pulse-to-pulse stability less than 1%. By employing a 1.5 mm-thick beta barium borate crystal, the frequency of the laser output is doubled to 515 nm, with an average power of 70 W, which corresponds to an optical-to-optical efficiency of 70%. This superior performance makes the system an attractive pump source for optical parametric chirped-pulse amplifiers in the near-infrared and mid-infrared spectral range. Combining the turn-key performance and the superior stability of the regenerative amplifier, the system facilitates the generation of a broadband, CEP-stable seed. Providing the seed and pump of the optical parametric chirped-pulse amplification (OPCPA) from one laser source eliminates the demand of active temporal synchronization between these pulses. This work presents a detailed guide to set up and operate a Yb:YAG thin-disk regenerative amplifier, based on chirped-pulse amplification (CPA), as a pump source for an optical parametric chirped-pulse amplifier.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Bioengineering; Chirped-pulse amplification; Issue 125; Laser; Nonlinear optics; Regenerative amplifier; Second harmonic generation; Thin-disk